Waterlogging and salinity effects on two Suaeda salsa populations - Song, Jie; Shi, Gongwei; Gao, Ben; Fan, Hai; Wang, Baoshan (Physiologia plantarum, 2011)
Adaptations to combined salinity and waterlogging stress were evaluated in two Suaeda salsa populations from different saline environments. Seedlings were exposed to 1, 200 and 600 mM NaCl in drained or waterlogged sand for 22 days in a glasshouse. Waterlogging did not significantly affect the K⁺/Na⁺ ratio or Cl⁻ concentration in leaves of either population. Adventitious roots were produced only by the inland population and under the waterlogged condition. X-ray microanalysis showed that S. salsa roots of the intertidal population accumulated more [Na⁺] and [Cl⁻] in both the cortex and stele than the roots of the inland population. The ability of roots to exclude Na⁺ and Cl⁻ was greater in the intertidal population than in the inland population, which may explain why leaves of the intertidal population accumulated less Na⁺ and Cl⁻ than the leaves of the inland population. The lower level of Cl⁻ than Na⁺ in leaves of both populations may result from the greater ability of roots to exclude Cl⁻ than Na⁺. These traits may help the two S. salsa populations adapt to their different saline environments.